Alport syndrome and autosomal dominant tubulointerstitial kidney disease frequently underlie end-stage renal disease of unknown origin—a single-center analysis. Issue 10 (29th April 2022) - Leenen, Esther; Erger, Florian; Altmüller, Janine; Wenzel, Andrea; Thiele, Holger; Harth, Ana; Tschernoster, Nikolai; Lokhande, Shanti; Joerres, Achim; Becker, Jan-Ulrich; Ekici, Arif; Huettel, Bruno; et al.
ABSTRACT: Background: The prevalence of end-stage renal disease of unknown etiology in adult patients is globally high and accounts for almost 20% of all dialysis patients. Recent studies have suggested that the percentage of adult patients with a causal genetic variant has been underestimated so far. Despite severe prognostic and therapeutic implications, awareness about prevalence and manifestations of genetic kidney diseases in adult renal patients is still limited. Methods: We recruited 58 individuals from 39 families at our transplantation center, fulfilling at least one of the following criteria: (i) unclear etiology of kidney disease, (ii) clinically suspected genetic kidney disease and (iii) positive family history for nephropathies. The cohort consisted of patients waitlisted for kidney transplantation and patients in the follow-up after transplantation. Detailed documentation of family history and phenotype was obtained before initiating gene panel sequencing of 479 nephropathy-associated genes. Results: With this study design, a molecular genetic diagnosis was established in one-third of all patients. Mutations in the collagen COL4A genes, and mutations in MUC1 and UMOD were the most frequent among all detected causal variants. Overall, rare genetic variants were detected in more than half of all cases. Conclusion: The combination of detailed phenotyping prior to next-generation sequencing diagnostics was highly efficient. Elucidating the underlying genetic causes in a cohort of adult renal patients has considerable clinical impact on medical management.